KOMPOSISI JENIS LARVA SIDAT (Anguilla spp.) YANG BERMIGRASI KE MUARA SUNGAI PROGO, YOGYAKARTA - Agung Budiharjo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Progo River is one of the rivers on the Java Island, which empties into the Indian Ocean, are became the entrance of the glass eels from the ocean. Glass eels were entering the river consists of several species. The aim of this research was to study of the species composition of glass eels that migrated into the estuary of the Progo River. Glass eels collected in the estuary in the year 2007–2009 at the lunar date 28 on at 20:00 until 04:00. In the period of 3 years, was successfully collected as many as 1.110 glass eels, which consisted of 3 species of Anguilla marmorata (31.17%), Anguilla bicolor bicolor (64,32%), and Anguilla nebulosa nebulosa (4.50%). Glass eels migrated into the estuary of Progo River during September to June. Glass eel of A. marmorata migrated to the estuary during September to June, A. bicolor bicolor migrated during October to June, and A. nebulosa nebulosa migrated to the estuary only during February to June.